Effects of leaf powder and ethanol extracts of selected plants on growth and incidence of onion pink root rot disease fungus (Phoma terrestris) - Mohammed, Rasha; Elbashir, O.; Abdalla, Y.F. (Gezira Journal of Agricultural Science, 2017)
Onion is one of the most important vegetable crops grown throughout the world and  it suffers from several diseases. Pink root rot disease caused by Phoma terrestris is a limiting factor for onion production. The aim of this study was to investigate the effects of basil, neem, lantana and argel extracts at 0.5,1.0 and 2.0 mg/l on fungal growth and disease incidence compared to the fungicide Premis FS (25%). All plant leaf extracts showed significant reductions in the  growth of Phoma terrestris . Basil showed a complete inhibition zone of  mycelial growth at 2.0 mg/l, followed by neem, lantana and the least inhibition was showed by argel. The fungicide Premis FS (25%), as a control, also caused a reduction of  mycelial growth . All treatments of   plant extracts and the fungicide Premis FS (25%) significantly reduced pink root rot disease compared to the control under greenhouse conditions. The highest reduction of the disease incidence was achieved by the fungicide Premis FS (25%), followed by the extracts of  basil, neem, lantana and the least effect was shown by argel. In conclusion, it is recommended to control onion pink root rot disease using basil leaf extract at 2.0 mg/l.            يعتبر محصول البصل من أهم المحاصيل المزروعة حول العالم ولكنه يعانى من عدد من الأمراض. يعتبر مرض عفن جذور البصل الوردي الذى يسببه الفطر   Phoma terrestris من العوامل المحددة لإنتاج البصل. هدفت الدراسة لمعرفة تأثير مستخلصات الريحان و الحرجل و اللانتانا والنيم بتركيزات صفر و1و2 مليجرام/لتر على نمو الفطر ونسبة الإصابة بالمرض في وجود المبيد الفطري Premis FS (25%)  كشاهد. أظهرت الدراسة نقصاً معنوياً في نمو الفطر Phoma terrestris . ثبط الريحان في التركيز العالي (2 مليجرام/لتر) نمو الفطر تثبيطاً كاملاً تلاه النيم و اللانتانا وأخيراً الحرجل. كذلك نتج عن معاملة النباتات المصابة  في المشتل بالمستخلصات النباتية نقصاً في نسبة الإصابة وكان المبيد الفطري Premis FS (25%) الأعلى في التأثير على معدل الإصابة ثم تلاه الريحان ثم النيم و اللانتانا واخرها الحرجل. خلصت الدراسة للتوصية بمعاملة البصل المصاب بمرض تعفن جذور البصل الوردي بمستخلص أوراق الريحان بالتركيز العالي 2 مليجرام/لتر